Preparation and characterization of oat hulls-filled-sodium alginate biocomposite microbeads for the effective adsorption of toxic methylene blue dye - Akgul, Irem; Isik, Birol; Ugraskan, Volkan (ELSEVIER, 2024)
In this work, the performance of oat hull-filled sodium alginate (SA-O) biocomposite microbeads in the adsorptive removal of methylene blue (MB) dye was examined. First, oat hulls were pulverized and biocomposite gels containing different weight ratios of oat hulls (10 %, 20 %, and 30 %, concerning the SA amount) were prepared by dispersing them in SA solution by ultrasonic homogenization method. Finally, gels were cross-linked by dropping into a 2 % CaCl2 solution. The study revealed that the optimal adsorbent dosage was 0.025 g/50 mL, pH was roughly 6-8, and the contact time was 120 min. According to isotherm models, the non-linear Sips and Langmuir model was more appropriate compare to other isotherms from error analysis, with a maximum adsorption capacity of 687.65 mg/g and 757.57 mg/g at 298 K, respectively. Furthermore, the non-linear kinetic data and error analyzes demonstrated that the process followed the pseudo-second-order kinetic. The adsorption process was exothermic (triangle H degrees=-17.71 kJ/mol) and spontaneous (triangle G degrees=-26.23 kJ/mol) at 298 K, based on thermodynamic characteristics. Furthermore, reusability investigations demonstrated that the adsorbent retained its performance with no major changes in characteristics. This work reveals that highly efficient, low-cost, sustainable, and eco-friendly SA-O composites with properties might be useful adsorbents for cationic dye adsorption.
Keywords: Adsorption; Methylene blue; Oat hulls; Sodium alginate; AVENA-SATIVA OAT; AQUEOUS-SOLUTIONS; REMOVAL; EQUILIBRIUM; COMPOSITE; KINETICS; BEADS; Biochemistry & Molecular Biology; Chemistry; Polymer Science